Procedure for quality inspection of welds based on macro-photogrammetric three-dimensional reconstruction. (October 2015) - Rodríguez-Martín, M.; Lagüela, S.; González-Aguilera, D.; Rodríguez-Gonzálvez, P.
Abstract: The results of visual inspection of welds depend on the visual ability of inspector. With the optical macro-photogrammetric low-cost procedure proposed in this paper only a digital single lens reflex camera with a macro-lens and a photogrammetric reconstruction software developed by the authors are needed for the generation of accurate and scaled 3D models of welds directly from images taken by a non-expert operator. This result eliminates the need of an in-situ assessment by the inspector, since it can be done directly using the 3D models generated, which the inspector can consult for the performance of all the measurements required by international standards. Highlights: Novel procedure for the quality evaluation of welds. The procedure is based on macro-photogrammetry to obtain a dense point cloud. Evaluation according to quality standards is possible with the proposed procedure. Direct measurements in the model allows the 3D characterization of surface cracks. Procedure for a fast and accurate inspection without displacement of the inspector.